Siderophore-mediated zinc acquisition enhances enterobacterial colonization of the inflamed gut - Judith Behnsen (Nature Portfolio, 2021)
Zinc is an essential cofactor for bacterial metabolism. Here, the authors show that the probiotic bacterium Escherichia coli Nissle 1917 utilizes the siderophore yersiniabactin as a zincophore, allowing the microbe to grow in zinc-limited media and to thrive in the inflamed gut.